Chiral adaptive recognition with sequence specificity of aromatic dipeptides in aqueous solution by an achiral cage. Issue 4 (6th January 2023) - Cheng, Lin; Tian, Ping; Duan, Honghong; Li, Qingfang; Song, Xiaowen; Li, Anyang; Cao, Liping
Abstract : An achiral TPE-based cage with the dynamic rotational conformation exhibits chiral adaptive recognition with sequence specificity for aromatic l -/d -dipeptides to achieve adaptive CD and CPL responses in aqueous solution. Abstract : Sequence-specific recognition of peptides and proteins by synthetic compounds or systems remains a huge challenge in biocompatible media. Here, we report the chiral adaptive recognition (CAR) with sequence specificity of aromatic dipeptides in a purely aqueous solution using an achiral tetraphenylethene-based octacationic cage (1 ) as both a molecular receptor and chiroptical sensor. 1 can selectively bind and dimerize aromatic dipeptides to form 1 : 2 host–guest complexes with high binding affinity (>10 10 M −2 ), especially up to ∼10 14 M −2 for TrpTrp. Given the dynamic rotational conformation of TPE units, achiral 1 can exhibit chiral adaptive responses with mirror-symmetrical circular dichroism (CD) and circularly polarized luminescence (CPL) spectra to enantiomeric dipeptides via supramolecular chirality transfer in the host–guest complexes. Furthermore, this CAR with sequence specificity of 1 can be applied for molecular recognition of TrpTrp- or PhePhe-containing tetrapeptides, polypeptides ( e.g., amyloid β-peptide1–20 and somatostatin), and proteins ( e.g., human insulin) with characteristic CD responses.